Rediseño de la instalación eléctrica de la planta de Envases Comeca S. A. - Elizondo-Picado, Kevin (Instituto Tecnológico de Costa Rica, 2018)
Like the first article of the National Electrical Code, the purpose of this project is to safeguard people and property against the risks arising from the use of electricity. These are aspects of security that most influence the development of this project, however, as engineers should seek a balance between the appropriate application of the regulation, without neglecting economic, logistical, and practical aspects. Now, the Envases Comeca S. A. plant is supplied with electric power through the distribution lines of the Compañía Nacional de Fuerza y Luz (CNFL) at a voltage of 13,8/7,62 kV with a demand of 1,5 MW. However, from August 2018 the energy will be delivered at a voltage of 34,5/19,9 kV. This change in the plant conditions not only forces a change in the rush equipment, but also opens an opportunity for the redesign and improvement of the electrical installation. A diagnosis is made of the rush and the main equipment that will be directly affected by the change, based on measurements taken in the field, ensuring that it complies with the minimum requirements established by the NEC 2008, and planning modifications if not. Engineering studies are carried out as the short-circuit study, the correct connections are determined for a good grounding system, a database is designed to optimize the information management and economic details are presented, always relevant to the realization of any project.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Rediseño; Corriente; Tierra; Manejo; Información